The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1097/brs.0000000000004703
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative HbA1c and Postoperative Outcomes in Spine Surgery

Abstract: Study Design. Systematic review and meta-analysis. Objective. To perform a systematic review and meta-analysis of previous studies on HbA1c in preoperative risk stratification in patients undergoing spinal procedures and provide an overview of the consensus recommendations. Summary of Background Data. Diabetes mellitus (DM) and hyperglycemia have been shown to be independent risk factors for increased surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…A recent study 1 revealed an association between higher preoperative HbA1c levels and an increased incidence of postoperative adverse events. Nevertheless, several concerns deserve further clarification.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study 1 revealed an association between higher preoperative HbA1c levels and an increased incidence of postoperative adverse events. Nevertheless, several concerns deserve further clarification.…”
mentioning
confidence: 99%
“…First, as described in Table 1, 1 it is evident that some included studies consisted of both diabetic and nondiabetic patients. Obviously, diabetic patients often exhibit substantially different HbA1c levels compared with nondiabetic individuals.…”
mentioning
confidence: 99%
“…First, we agree that the distinction between diabetic and nondiabetic patients is critical. The two studies included in the meta-analysis compared mean difference in hemoglobin A1C (HbA1c) level between Surgical Site Infection and non-Surgical Site Infection group included both diabetic and nondiabetic populations 1 . One study was excluded from the meta-analysis because it included diabetic patients only as this would have been incongruent with the other two studied and had a higher average HbA1c which potentially could have confounded the meta-analysis.…”
mentioning
confidence: 99%
“…Preoperative glycemic control, as reflected by HbA1c levels, is a critical factor in reducing the risk of postoperative complications, including infections. Studies have shown that achieving target HbA1c levels before surgery can significantly improve outcomes 10 . Therefore, it is essential to discuss and include analyses related to the optimal level of HbA1c that should be controlled before spine surgery.…”
mentioning
confidence: 99%